Superficial Epidermolytic Ichthyosis: Clinical and Histopathological Features in Two Siblings - Shah, Pooja; Padhiar, Bela (Nepal Journal of Dermatology, Venereology & Leprology, 2025)
Superficial epidermolytic ichthyosis (SEI), a type of keratinopathic ichthyosis (KPI) caused by mutations in the K2e gene, is clinically characterized by superficial blistering, hyperkeratosis predominantly involving flexures and joints, Mauserung phenomenon and epidermolytic hyperkeratosis (EHK) on ultrastructural studies. Though it has been known to mankind for ages, very few families afflicted with this disease are described in the literature and its exact prevalence in the Indian population is yet undetermined. Through this case report, we wanted to highlight its various peculiar manifestations and reiterate the importance of meticulous clinical evaluation and clinicopathological correlation, especially in resource-limited settings, for effective patient management.